TRANSITIVITY SHIFTS FOUND IN THE TRANSLATION OF INDONESIAN NEWSLETTER “PASAR TRADISIONAL DI ERA PERSAINGAN GLOBAL” INTO ENGLISH - Desak Nyoman Sri Rahayu Sugianti (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
The translation of Indonesian transitivity into English involves the identification of a process type, of way participants are presented (as actor, goal, affected entity, etc.), and the circumstances in which the process takes place. Since SL and TL may differ because of a large number of factors, there are wide of potential shifts in the translation of transitivity. This research applies qualitative approach in which the data was analyzed descriptively. The data was taken from bilingual newsletter (Indonesian-English) entitled “Pasar Tradisional di Era Persaingan Global”; Traditional Market in the Era of Global Competition”.They are the theory of transitivity process categories by Halliday (1985), types of transitivity shifts by Perez (2007).The data was collected through observation methods by comparing, note taking, marking, classifying, and identifying. The transitivity shifts occurred in categories of lexical unit and the syntactic structure. Meanwhile, the transitivity shifts caused by the different interpretation by the translators in order to provide a different picture to the reader without changing the message to be conveyed. Based on the analysis, there are no significant impacts of the transitivity shifts found.